A designated trauma social worker improves coordination of patient care by coordinating ancillary consults. (16th March 2022) - Dhillon, Navpreet K.; Kolus, Riley C.; Patel, Kavita A.; Conde, Geena; Perez, Jazmin; Holtz, Heidi; Ley, Eric J.
ABSTRACT: Trauma patients face unique challenges that require coordination by social workers knowledgeable in the intricacies of trauma patient psychosocial support which is often achieved by obtaining ancillary consultations. The impact of employing a designated trauma social worker (DTSW) in the utilization of these consults has not been described. A retrospective review was conducted of trauma patients admitted to an academic, urban Level 1 trauma center. The pre-intervention cohort (n = 272) corresponded to patients admitted before the presence of a DTSW (01/2013 to 06/2013), while the post-intervention cohort (n = 282) corresponded to patients admitted afterward (09/2015 to 01/2016). Data collection included demographics, injury profile, and types of interdisciplinary or therapy consultations. Post-intervention patients were found to be older and admitted with more injuries. Supportive care, physical therapy and occupational therapy consultations were more likely to be obtained in the post-intervention cohort. Hospital length of stay remained unchanged. This study suggests that the implementation of a DTSW significantly facilitates the utilization of interdisciplinary consultations. Length of stay remains unchanged, suggesting that a DTSW helps to coordinate care in a timely manner without increasing the hospital stay. DTSW implementation may be considered in trauma centers where one does not currently exist.